Captain Marvel [videorecording (DVD)] - Larson, Brie, 1989-; Chan, Gemma, 1982-; Mendelsohn, Ben; Jackson, Samuel L. (Marvel Studios, 2019)
Set in the 1990s, this is an all-new adventure from a previously unseen period in the history of the Marvel Cinematic Universe. It follows the journey of Carol Danvers as she becomes one of the universe's most powerful heroes. While a galactic war between two alien races reaches Earth, Danvers finds herself and a small cadre of allies at the center of the maelstrom.